The larva of Tricholeon relictus Hölzel & Monserrat, 2002 a synanthropic antlion (Neuroptera, Myrmeleontidae) - Acevedo, Fernando; Badano, Davide; Monserrat, Víctor J. (Zootaxa, 2014)
The larva of Tricholeon relictus, a Spanish endemic antlion of Afrotropical affinities, is described and illustrated for the first time also providing a comparison with the only other European member of the tribe Dendroleontini, Dendroleon pantherinus. The larva of this species is synanthropic but probably originally lived in cave-like habitats.